2018
DOI: 10.3390/nu10080971
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Patterns and Quality of Life in Older Adults: A Systematic Review

Abstract: Dietary patterns may be related to quality of life (QoL) of older adults, although evidence from literature is conflicting. The demographic shifts toward ageing populations in many countries increases the importance of understanding the relationship between diet and QoL in older adults. This review was designed to investigate associations between dietary patterns and QoL in older adults. The systematic review followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
143
1
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 246 publications
(165 citation statements)
references
References 93 publications
15
143
1
6
Order By: Relevance
“…Only one study that used a nutrition intervention provided more detailed and tailored advice [49]. Diet patterns have been shown to influence QoL in older adult populations [85] but little research is available that tests the differential effects of tailored PA, diet or a combination of both. More research is necessary, particularly randomized controlled trials, to determine the presence and strength of this link among the older adult LWBC population.…”
Section: Discussionmentioning
confidence: 99%
“…Only one study that used a nutrition intervention provided more detailed and tailored advice [49]. Diet patterns have been shown to influence QoL in older adult populations [85] but little research is available that tests the differential effects of tailored PA, diet or a combination of both. More research is necessary, particularly randomized controlled trials, to determine the presence and strength of this link among the older adult LWBC population.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, knowledge of the lifestyle factors that contribute to people having a better quality of life it should be one of the main priorities of health systems [ 3 , 5 , 6 ]. Diet is one of such lifestyle factors that could have the greatest impact on health and quality of life [ 7 , 8 , 9 , 10 ]. Currently, new evidence is emerging on the importance of making more specific nutritional recommendations for each person or group of people depending on their characteristics and needs [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although the burden of following a restrictive diet has the potential to impair QOL [52], it has been found that HD patients who control their diet benefit from reduced symptom burden and enhanced general health and wellbeing [53]. In non-dialysis populations, following healthy dietary patterns has also been associated with improved QOL [54,55]. In the African American Study of Kidney Disease and Hypertension, both lower mental and physical health scores were associated with increased risk of cardiovascular events among blacks with hypertensive CKD.…”
Section: Discussionmentioning
confidence: 99%